2021
DOI: 10.1371/journal.pone.0245509
|View full text |Cite
|
Sign up to set email alerts
|

Has loneliness and poor resilient coping influenced the magnitude of psychological distress among apparently healthy Indian adults during the lockdown? Evidence from a rapid online nation-wide cross-sectional survey

Abstract: Background The burden of psychological distress is increasing with the spread of the pandemic and also with the enforcement of its containment measures. The aim of this research was to determine the proportion of self-reported psychological distress, loneliness and degrees of resilient coping, and to also investigate the relationship of loneliness, coping and other variables with psychological distress among apparently healthy Indians during nation-wide lockdown period. Methods A cross-sectional, region-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…for China see [2]. These 600 publications do not only comprise country-specific studies, on countries like Italy [3][4][5], Spain [6], Nepal [7], China [8], Africa [9], and India [10], but also cross-sectional studies accounting for mental impacts on the overall population e.g. [11,12] as well as on specific socio-demographic groups such as students [13], vulnerable groups like the elderly [14] and doctors (e.g.…”
Section: Current State Of Research On the Psychological Impacts Of Th...mentioning
confidence: 99%
“…for China see [2]. These 600 publications do not only comprise country-specific studies, on countries like Italy [3][4][5], Spain [6], Nepal [7], China [8], Africa [9], and India [10], but also cross-sectional studies accounting for mental impacts on the overall population e.g. [11,12] as well as on specific socio-demographic groups such as students [13], vulnerable groups like the elderly [14] and doctors (e.g.…”
Section: Current State Of Research On the Psychological Impacts Of Th...mentioning
confidence: 99%
“…Following with this, half of the sample saw COVID-19 news on social media as worrying, which the researchers point to as one stressor that can explain the trend of declining mental health during the pandemic. Lahiri et al (2021) had a similar discovery, finding in a survey of 1,249 Indian adults that those who were exposed to COVID-19 news on social media were more likely to be distressed. This possible link between mental health and social media may help explain the preventive measures that teens take, which is the focus of this study.…”
Section: Covid-19 Attitudesmentioning
confidence: 71%
“…While at home, youth were left with social media to safely interact with others, which is a practice that is still strong up to this present study (Cauberghe et al, 2021). This raises an especially important concern of how they base their health decisions for COVID-19 on social media, since much of the existing literature has found that people use it as the predominant source of information on the disease (Aynalem et al, 2021;Campbell et al, 2021;Lahiri et al, 2021;Nemat et al, 2021;Singh & Balhara, 2021). However, none of these studies have collected information on what social media platforms were specifically used, which is problematic given that the platforms moderate COVID-19 content differently, as explained in a Harvard study by Krishnan et al (2021).…”
Section: Introductionmentioning
confidence: 92%
“…Im Januar 2021 ergab die Suche nach den Begriffen "mental resilience COVID" in der Literaturdatenbank PubMed.gov 25 empirische Studien, die mit Fragen zu Resilienz und mentaler Gesundheit während der Corona-Pandemie, zwischen Februar und August 2020 befasst waren. Diese Studien, zumeist umgesetzt über querschnittliche Online-Umfragen, umfassten zusammen insgesamt über 76000 Teilnehmende und wurden in China und anderen asiatischen Ländern [31][32][33][34][35][36][37], dem Irak [38], der Türkei [39,40], Israel [41], europäischen Ländern [42][43][44][45][46][47][48], den USA [49][50][51] und Kanada [52] durchgeführt. Die folgenden Ergebnisse wurden vielfach berichtet: Depressive und Angstsymptome hatten im Vergleich zu Populationsnormen zugenommen.…”
Section: Steigende Relevanz Der Resilienz Während Der Corona-pandemieunclassified